If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3*(2x-7)-(3x+3)=4*(5-2x)
We simplify the equation to the form, which is simple to understand
3*(2x-7)-(3x+3)=4*(5-2x)
Reorder the terms in parentheses
+(+6x-21)-(3x+3)=4*(5-2x)
Remove unnecessary parentheses
+6x-21-(+3x+3+)=+4+*(+5-2x+)
Remove unnecessary parentheses
+6x-21-3x-3=4*(5-2x)
Reorder the terms in parentheses
+6x-21-3x-3=+(+20-8x)
Remove unnecessary parentheses
+6x-21-3x-3=+20-8x
We move all terms containing x to the left and all other terms to the right.
+6x-3x+8x=+20+21+3
We simplify left and right side of the equation.
+11x=+44
We divide both sides of the equation by 11 to get x.
x=4
| 8x/15-2x/5+3x/10-33=2x/15-x/5+5 | | x-55= | | 21-2(x-3)=48-4(3-x)-7x | | 4ab+bc=35 | | 8a+9=58 | | 3x^2+y^2=28 | | x^2=14x-15 | | 3p+5a+9=58 | | X^2-y^2-2xy=0 | | 6x-5y+2x-3y+2x= | | 8x+85=105 | | 4x^2=-100x | | 8x+3=-3x+3+11x | | 6m+m-3rpm= | | 6m+m-3rp+2rpm= | | 0=[x-(1+2i)][x-(1-2i)](x-1)(x+2) | | 0=[x-(2+3i)][x-(2-3i)](x+1)(x-2) | | -3x-11=5x+21 | | 0=[x-(2+2i)][x-(2-2i)](x+1)(x-2) | | ydx+(x+y)st=0 | | y=3x^4-4x^3-12x^2+2 | | 3.2=-6u+22.4 | | 42=4a+9 | | 7(x-8)+17=4(x-6) | | 0.7(X+20)+0.9x=78 | | 8.75=u | | -2x+2=-2(2x+5) | | 2(5x+1)=6x-(2-4x) | | 0.4(x-6)=4.0 | | y=5x^2-6x | | 6-8x-2=-48+3x-14 | | 3x=4+3x-1 |